2020
DOI: 10.5209/psic.72022
|View full text |Cite
|
Sign up to set email alerts
|

Psicoterapia Centrada en el Sentido: Una revisión acerca de estrategias psicoterapéuticas para el tratamiento del paciente con cáncer

Abstract: Objetivo: presentar las estrategias psicoterapéuticas utilizadas en el tratamiento de pacientes con cáncer, cuya finalidad sea trabajar el sentido de la vida. Método: Se realizó una revisión sistemática inscrita en el registro PROSPERO con el número CRD42019132385, siguiendo el método PRISMA, en las bases Lilacs, Medline, Scopus y Web of Science. Resultados: Se incluyeron 11 artículos publicados entre 2014 y 2020. La Psicoterapia Centrada en el Sentido (PCS) es la estrategia psicoterapéutica más utilizada y ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…A subtle trend can be noted in the six results at the foot of the graph for publications with authors from different countries (3 or more) (Figure 8b). Additionally, it was observed that Brazilian authors also published articles in both English (e.g., Cunha et al, 2022), and Spanish (e.g., Medeiros et al, 2020).…”
Section: C) Authors and Country Of Originmentioning
confidence: 99%
See 1 more Smart Citation
“…A subtle trend can be noted in the six results at the foot of the graph for publications with authors from different countries (3 or more) (Figure 8b). Additionally, it was observed that Brazilian authors also published articles in both English (e.g., Cunha et al, 2022), and Spanish (e.g., Medeiros et al, 2020).…”
Section: C) Authors and Country Of Originmentioning
confidence: 99%
“…Moreover, in the context of the science of the psyche, the topic is also explored through a variety of epistemological approaches ranging from existentialist perspectives (e.g., Vos et al, 2015) to humanist (e.g., Edberg et al, 2023), psychoanalytical (e.g., Mendes, 2018), phenomenological (e.g., Larsson & Bolmsjö, 2017), and positive (e.g., Wong, 2017) perspectives and, via the logotherapy approach (e.g., Roehe, 2006;Nassif et al, 2010;Medeiros et al, 2020), a dimension centered explicitly on the question of meaning. This bears witness to the global dimension and the importance of the topic in question to the field of mental health, justifying it not only as the focal point of diverse studies but also in its cross-sectional approach in a variety of contemporary studies in psychology.…”
Section: Introductionmentioning
confidence: 99%